Active Aging and Elderly’s Quality of Life: Comparing the Impact on Literature of Projects Funded by the European Union and USA - Kirilov, I (Clin Pract Epidemiol Ment Health, 2018)
BACKGROUND: The objective of this research is to verify whether European projects on Active Aging (AA) and Elderly Quality of Life (Qol) funded by the Seventh Framework Programme (FP7) produce an impact on literature similar to projects funded by the National Health Institute (NHI) of the United States on international literature using well-known bibliometric indicators. This effort may be useful in developing standardized and replicable procedures. METHODS: Fifteen randomly selected projects on AA and Elderly Qol concluded in August 2017 and funded by FP7 were compared to similar projects funded by the US NHI with reference to papers published (Scopus and Scholar), papers published in Q1 journals, and the number of citations of the papers linked to the projects. RESULTS: In all the indicators considered, the European projects showed no difference with the US NHI projects. CONCLUSIONS: The EU-funded AA and Qol Elderly projects have an impact on scientific literature comparable to projects funded in the United States by the NHI Agency. Our results are consistent with the data on general medical research, which indicates that, European research remains at a high level of competitiveness. In this experimental study, our methodology appeared to be convincing and reliable and it could be applied to the extent of the impact of more extensive research areas. Our research did not evaluate the relationship between funding required by research and scientific productivity.